Perhitungan Larva Aedes spp. Berdasarkan Hasil Rearing Ovitrap Berwarna Dalam Ruangan di Kelurahan Malalayang Satu Barat Kota Manado - Stephen Stephen; Angle M. H. Sorisi; Josef S. B. Tuda (Universitas Sam Ratulangi, 2024)
Abstract: Dengue hemorrhagic fever (DHF) is still a health problem in Indonesia including Manado. Ovitrap is a dengue vector control method that is quite sensitive and proven to reduce vector density safely and economically. Color is one of the factors that plays an important role in the effectiveness of ovitrap, albeit, there are still few reported studies related to Aedes spp egg viability, especially by rearing ovitrap with different colors. This study aimed to determine the percentage of Aedes spp larvae found in each color of the indoor ovitrap rearing results. This was a descriptive study with a cross-sectional design using ovitraps at Malalayang Satu Barat Sub-district. The results showed the percentages of Aedes spp eggs hatched in the ovitraps, as follows: yellow ovitrap 94%, blue 92%, white 84%, black 82%, red 70%, and transparent 36%. The average number of eggs per ovitrap, as follows: black (17.00), white (12.56), red (10.78), yellow (10.60), blue (7.70), and transparent (3.11) with ovitrap index (OI) =74.72%. In conclusion, the criteria of egg density in Malalayang Satu Barat Sub-District is high. Black ovitrap has the highest number of eggs and the least is transparent ovitrap, however, yellow and blue ovitraps have the highest percentages of hatching eggs. Keywords: dengue hemorrhagic fever; Aedes spp. larva; ovitrap color; rearing; ovitrap index Abstrak: Demam berdarah dengue (DBD) masih menjadi masalah kesehatan di Indonesia, termasuk kota Manado. Ovitrap merupakan metode pengendalian vektor DBD yang cukup sensitif dan terbukti menurunkan kepadatan vektor secara aman dan ekonomis. Warna menjadi salah satu faktor penting keefektifan ovitrap, namun sedikit studi tentang viabilitas telur khususnya melakukan rearing ovitrap dengan warna berbeda. Penelitian ini bertujuan untuk mengetahui jumlah persentase larva Aedes spp. yang terdapat pada setiap warna hasil rearing ovitrap dalam ruangan. Jenis penelitian ialah deskriptif dengan desain potong lintang menggunakan ovitrap di Kelurahan Malalayang Satu Barat. Hasil penelitian mendapatkan persentase telur menetas pada ovitrap kuning sebesar 94%, biru 92%, putih 84%, hitam 82%, merah 70%, dan transparan 36%. Rerata jumlah telur per ovitrap hitam (17,00), putih (12,56), merah (10,78), kuning (10,60), biru (7,70), dan transparan (3,11) dengan ovitrap index (OI) =74,72%. Simpulan penelitian ini ialah kepadatan telur Kelurahan Malalayang Satu Barat tergolong kriteria tinggi. Ovitrap hitam memiliki telur terbanyak dan ovitrap transparan yang paling sedikit, namun ovitrap kuning dan biru memiliki persentase telur menetas yang paling tinggi. Kata kunci: demam berdarah dengue; larva Aedes spp.; warna ovitrap; rearing; ovitrap index